2007
DOI: 10.3199/iscb.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Mexican and Central American Pinguicula (Lentibulariaceae) based on internal transcribed spacer (ITS) sequence

Abstract: ABSTRACT. The internal transcribed spacer (ITS) region of 18S-26S nuclear ribosomal DNA (nrDNA) in 36 species of Pinguicula (Lentibulariaceae) in Mexico and Central America, most of which are endemic to Mexico, was sequenced. Based on the ITS results, those species of Pinguicula studied were divided into three clades. In general, these cledes do not agree with the current conventional classification proposed by various authors except for Clade I. Clade I includes only two species belonging to section Isoloba, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…The general topology of the ITS phylogenetic tree obtained in this study is, in general, congruent with the phylogenetic reconstructions of the Pinguicula genus based on ITS sequences from previous papers [51,85]. We recovered two major clades of Central American and Mexican species: the P. emarginata-P. moctezumae clade and P. agnata-P. gigantea clade, as well as taxon P. albida, corresponding to clades VII, VIII, and IX, respectively, according to Shimai et al [51].…”
Section: Evolution Of Floral Characters: Synapomorphies Vs Homoplasiessupporting
confidence: 89%
See 1 more Smart Citation
“…The general topology of the ITS phylogenetic tree obtained in this study is, in general, congruent with the phylogenetic reconstructions of the Pinguicula genus based on ITS sequences from previous papers [51,85]. We recovered two major clades of Central American and Mexican species: the P. emarginata-P. moctezumae clade and P. agnata-P. gigantea clade, as well as taxon P. albida, corresponding to clades VII, VIII, and IX, respectively, according to Shimai et al [51].…”
Section: Evolution Of Floral Characters: Synapomorphies Vs Homoplasiessupporting
confidence: 89%
“…The position of P. esseriana was unresolved in our analysis. Shimai et al [51,85], in previous analyses based on ITS sequences, placed P. esseriana in clade III/VIII (which corresponds to the P. agnata-P. gigantea clade in this work) with 52% and 57% bootstrap support, respectively. P. esseriana has long-spurred and colored flowers with visible yellow blotches at the entrance to the spur, indicating psychophily pollination syndrome.…”
Section: Evolution Of Floral Characters: Synapomorphies Vs Homoplasiessupporting
confidence: 56%
“…Degtjareva et al [42] and Kondo & Shimai [43] analysed taxa mainly from the temperate Northern Hemisphere using the internal transcribed spacer (ITS) region, and they showed that taxa forming rootless hibernacula in the section Pinguicula were monophyletic. Shimai & Kondo [44] analysed the ITS (ITS-1, 5.8S, and ITS-2) regions of 36 species from Mexico and Central America and suggested that the species were monophyletic, although Casper [3] had divided them into three subgenera. Overall, those phylogenetic analyses were not consistent with the morphology-based classification.…”
Section: Plos Onementioning
confidence: 99%
“…[14] by means of ITS region (nuclear internal transcribed spacers and small ribosomal gene, ITS T , nrDNA). The ITS T resulted much more informative than plastid markers, and was also used in a couple of studies focused on the species from Northern hemisphere [15] and focused on central American and Cuban taxa [16, 17]. In the above-cited studies, a few Italian endemic species, such as P .…”
Section: Introductionmentioning
confidence: 99%
“…Our marker choice is supported by: (1) high variability and discriminating capabilities of this molecular marker among Pinguicula taxa as already shown by Degtjareva et al . [14], Kondo & Shimai [15], Shimai & Kondo [16] and Shimai et al . [17]; (2) a complete GenBank nrDNA- Pinguicula database to be used for an exhaustive phylogenetic reconstruction; (3) completeness of information as a consequence of the biparental inheritance of nrDNA [6, 26, 27, 28].…”
Section: Introductionmentioning
confidence: 99%